Cationic liposome-DNA complex-based immunotherapeutic and immunization strategies for control of la Crosse virus and Leishmania major infections - Arthun, Erik Norden, author; Dow, Steven, advisor; Foy, Brian, committee member; Lappin, Michael, committee member; Callan, Robert, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: vaccine; aerosol; CLDC; immunotherapy; La Crosse virus; Leishmania major